Classical and non-classical Lie symmetry analysis, conservation laws and exact solutions of the time-fractional Chen-Lee-Liu equation - Hashemi, M. S.; Haji-Badali, A.; Alizadeh, F.; İnç, Mustafa (Springer Heidelberg, 2023)
The current work deals with the classical and non-classical Lie group analysis for the fractional type system of nonlinear Chen-Lee-Liu (CLL) equations. The invariance surface condition is imposed to this system of fractional differential equations to find non-classical generators. Non-classical and classical Lie symmetry analysis are used to similarity reductions of this system. Corresponding exact solutions are obtained for the extracted generators in both classical and non-classical senses. Convergence of the obtained solutions when fractional order tends to the integer one, is graphically checked. Finally, the conservation laws are investigated for the system of time-fractional CLL equations, specially for the non-classical vector fields.
Keywords: Lie group; System of time-fractional PDEs (SFPDEs); Non-classical symmetry; Classical symmetry; Conservation laws; Chen-Lee-Liu equation